2015
DOI: 10.1186/s13104-015-1233-6
|View full text |Cite
|
Sign up to set email alerts
|

Composite pheochromocytoma of the adrenal gland: a case series

Abstract: BackgroundComposite pheochromocytoma is a rare pathological condition characterized by elements of both pheochromocytoma and neurogenic tumors. However, detailed clinical outcomes of this tumor have not been fully shown. From 2007 to 2013, we experienced three cases of adrenal composite pheochromocytoma. In this report, we investigate the clinicopathological features of these three cases of composite pheochromocytoma and compare them with previously reported cases.Case presentationsCases 1 and 2 were a 29-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…Composite pheochromocytoma-ganglioneuroblastoma is an extremely rare tumor (1,(6)(7)(8)(9)(10)(11)(12), given this unusual association that sparked interest in reporting the case; we confirm its importance to be source of studies and possible new treatments.…”
Section: Considerationssupporting
confidence: 59%
“…Composite pheochromocytoma-ganglioneuroblastoma is an extremely rare tumor (1,(6)(7)(8)(9)(10)(11)(12), given this unusual association that sparked interest in reporting the case; we confirm its importance to be source of studies and possible new treatments.…”
Section: Considerationssupporting
confidence: 59%
“…A review of the literature identified fewer than 100 reported cases of adrenal ganglioneuroma in the last 20 years, many of which are found incidentally on imaging, or with non‐specific symptoms of abdominal discomfort, elevated blood pressure or gastrointestinal symptoms. In a small percentage of these cases, the lesions were found to be composite pheochromocytoma–ganglioneuromas, which occasionally present with symptoms related to hormone secretion . We have also identified a similar case of a retroperitoneal extra‐adrenal ganglioneuroma involving multiple vessels that was also excised successfully with preservation of neighbouring anatomical structures due to a plane of cleavage being easily found between the tumour pseudocapsule and adjacent structures …”
mentioning
confidence: 78%
“…To date, less than 50 cases of composite pheochromocytoma have been reported [7,8,9]. Preoperative detection of a composite pheochromocytoma ganglioneuroma is difficult because of the low incidence of ganglioneuroma and because the symptoms are not different from those of typical pheochromocytomas [10].…”
Section: Discussionmentioning
confidence: 99%